Downregulation of myostatin pathway in neuromuscular diseases may explain challenges of anti-myostatin therapeutic approaches. Issue 1 (December 2017) - Mariot, Virginie; Joubert, Romain; Hourdé, Christophe; Féasson, Léonard; Hanna, Michael; Muntoni, Francesco; Maisonobe, Thierry; Servais, Laurent; Bogni, Caroline; Panse, Rozen; Benvensite, Olivier; Stojkovic, Tanya; et al.
Abstract Muscular dystrophies are characterized by weakness and wasting of skeletal muscle tissues. Several drugs targeting the myostatin pathway have been used in clinical trials to increase muscle mass and function but most showed limited efficacy. Here we show that the expression of components of the myostatin signaling pathway is downregulated in muscle wasting or atrophying diseases, with a decrease of myostatin and activin receptor, and an increase of the myostatin antagonist, follistatin. We also provide in vivo evidence in the congenital myotubular myopathy mouse model (knock-out for the myotubularin coding geneMtm1 ) that a down-regulated myostatin pathway can be reactivated by correcting the underlying gene defect. Our data may explain the poor clinical efficacy of anti-myostatin approaches in several of the clinical studies and the apparent contradictory results in mice regarding the efficacy of anti-myostatin approaches and may inform patient selection and stratification for future trials. Drugs targeting myostatin reverse muscle wasting in animal models, but have limited efficacy in patients. The authors show that the myostatin pathway is downregulated in patients, possibly explaining the poor outcome of anti-myostatin approaches, and that it can be reactivated by correcting disease-causing mutations in mice.